2006
DOI: 10.5194/nhess-6-629-2006
|View full text |Cite
|
Sign up to set email alerts
|

A neural network model for short term river flow prediction

Abstract: Abstract. This paper presents a model using rain gauge and weather radar data to predict the runoff of a small alpine catchment in Austria. The gapless spatial coverage of the radar is important to detect small convective shower cells, but managing such a huge amount of data is a demanding task for an artificial neural network. The method described here uses statistical analysis to reduce the amount of data and find an appropriate input vector. Based on this analysis, radar measurements (pixels) representing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
3
21
0
Order By: Relevance
“…These results were consistent with the findings of previous studies (Teschl and Randeu, 2006;Li et al, 2012;Wu and Chau, 2010), which showed the ability of the ANN model to determine an atmospheric link between SST anomalies and precipitation over the inland area of the Persian Gulf.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results were consistent with the findings of previous studies (Teschl and Randeu, 2006;Li et al, 2012;Wu and Chau, 2010), which showed the ability of the ANN model to determine an atmospheric link between SST anomalies and precipitation over the inland area of the Persian Gulf.…”
Section: Discussionsupporting
confidence: 92%
“…Since large differences existed in the means and variations between the parameters, the data were normalized (Trenberth, 1994;Teschl and Randeu, 2006;Guérémy, 2012) before they were used in the model. After normalization, all time series of monthly rainfall and climate indices were in the range of 0 and 1 (see Appendix: Eq.…”
Section: Description Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A MLP is a so-called 'feedforward' neural network because all the information flows in one direction. The neurons of one layer are connected with the neurons of the following layer without feedback (Teschl and Randeu, 2006). The weights adjustment was performed by a back propagation algorithm: weights are modified to reduce the error occurrence between actual and desired network outputs backward from the output layer to the input layer (Backhaus et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of this study a multi-layer perceptron NN design is applied, which is known as a "feed-forward" NN with all information flowing in one direction. The neurons of one layer are connected with the neurons of the following layer without feedback (Teschl and Randeu, 2006). The signals flowing on the connections are scaled by adjustable parameters, which are called weights (Principe et al, 2000).…”
Section: Methodsmentioning
confidence: 99%